BME-Y5V Materials Prepared by Solid State Technology - G. Koebrugge; K. Albertsen; I. Hayashi (Active and Passive Electronic Components)
In this paper the properties of BME-Y5V dielectric powders prepared by solid state technology is described. A new formulation is presented, suitable in multilayer capacitors for layers down to 4μm . The material shows good reliability due to the presence of magic dopants in this formulation. The effect of magic dopants in dielectric formulations is discussed.